2018
DOI: 10.1126/science.aao4669
|View full text |Cite
|
Sign up to set email alerts
|

A dust-enshrouded tidal disruption event with a resolved radio jet in a galaxy merger

Abstract: Tidal disruption events (TDEs) are transient flares produced when a star is ripped apart by the gravitational field of a supermassive black hole (SMBH). We have observed a transient source in the western nucleus of the merging galaxy pair Arp 299 that radiated >1.5 × 10 erg at infrared and radio wavelengths but was not luminous at optical or x-ray wavelengths. We interpret this as a TDE with much of its emission reradiated at infrared wavelengths by dust. Efficient reprocessing by dense gas and dust may explai… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

12
185
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
8
1

Relationship

3
6

Authors

Journals

citations
Cited by 166 publications
(197 citation statements)
references
References 87 publications
12
185
0
Order By: Relevance
“…More recently, similar X-ray events have been detected with Chandra and XMM-Newton based on dedicated searches or serendipitous discoveries (Esquej et al 2007(Esquej et al , 2008Saxton et al 2012;Auchettl et al 2017). Interestingly, Mattila et al (2018) reported the infrared discovery of a TDE in the merging galaxy pair Arp299, in which the optical emission is strongly obscured by dust. In this case, a expanding relativistic jet produced by the accretion of stellar debris on the SMBH has been clearly detected and resolved by radio VLBI observations.…”
Section: Introductionmentioning
confidence: 72%
“…More recently, similar X-ray events have been detected with Chandra and XMM-Newton based on dedicated searches or serendipitous discoveries (Esquej et al 2007(Esquej et al , 2008Saxton et al 2012;Auchettl et al 2017). Interestingly, Mattila et al (2018) reported the infrared discovery of a TDE in the merging galaxy pair Arp299, in which the optical emission is strongly obscured by dust. In this case, a expanding relativistic jet produced by the accretion of stellar debris on the SMBH has been clearly detected and resolved by radio VLBI observations.…”
Section: Introductionmentioning
confidence: 72%
“…The possibility of a weaker nonrelativistic outflow cannot be excluded, but the limit places strict requirements that the radio luminosity from any an outflow does not exceed that seen in nearby events like ASASSN-14li (Alexander et al 2016;van Velzen et al 2016). Further observations will be required to rule out an off-axis jet such as that seen in Arp 299-B (Mattila et al 2018) 2012b). However, most TDEs are not bright in the radio.…”
Section: Radio Observationsmentioning
confidence: 99%
“…This number is made uncertain to the degree that the distribution of stellar orbits near an AGN is systematically different from the center of an inactive galaxy, and that the black hole in a galaxy with an AGN tends to be more massive than a galaxy without one (see also Karas & Šubr 2007;Kennedy et al 2016). Because both TDEs and AGNs vary on timescales of weeks to months, and because a TDE in an AGN presents less contrast against the prior state of the system than a TDE in an inactive galaxy, deciding whether an increase in brightness is due to a TDE or is merely AGN variability is not trivial (Komossa 2015;Kankare et al 2017;Auchettl et al 2018;Trakhtenbrot et al 2019b); indeed, there are a number of cases in which the correct identification of a particular episode of variation is disputed (e.g., Campana et al 2015;Grupe et al 2015;Merloni et al 2015;Saxton et al 2015;Blanchard et al 2017;Lin et al 2017;Wyrzykowski et al 2017;Mattila et al 2018;Shu et al 2018). It is therefore of interest to see if TDEs in AGNs have distinctive observational characteristics that allow us to recognize them more reliably.…”
Section: Introductionmentioning
confidence: 99%